DINAMIKA PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA - Auwaliyah, Rofiati; M. Syarif; Muhammad Ali Rohmad (Atta'dib Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the dynamics of AI use in Islamic Religious Education (PAI) learning. This research employed a qualitative method with a case study approach. Data collection procedures used observation, interviews, and documentation, while data analysis procedures involved data condensation, data display, and conclusion drawing. The research findings indicate that the use of AI in PAI learning at SMAN 1 Gedeg has brought significant changes for both teachers and students. The main findings show that AI accelerates the creation of teaching materials, expands references, supports independent learning, and increases efficiency and interactivity in assignments and evaluations. The presence of AI also boosts students' confidence in seeking new knowledge and encourages them to explore information beyond conventional teaching materials. The adaptive and contextual use of AI has been proven to be adjustable to learning needs, although the role of the teacher remains crucial as a validator and gatekeeper of material, especially to maintain the authenticity of knowledge delivery in accordance with Islamic tradition. However, this study also identified several weaknesses, such as limited data on Quranic verses and hadith, difficulty in understanding complex religious concepts, and the potential for student dependence on AI, which can reduce critical thinking skills, self-reliance, and interest in reading. Additionally, there is a risk of decreased learning motivation and misuse of AI outside of the educational context. Other weaknesses noted include limited internet access and the need for supervision to ensure that information from AI remains aligned with Islamic values and appropriate religious education practices.